Overmacht Dalam Perjanjian Sewa Menyewa Alat Berat: Suatu Analisis Penyelesaian Sengketa - Romadhoni, Muhammad Masruri; Bisyri, Muhammad Hasan; Setiawati, Lilis (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to determine the resolution of internal overmacht disputes heavy equipment rental agreement at PT. Setya Perkasa Graha Aditama. And aims to explain the legal consequences of dispute resolution overmacht towards the parties in the rental agreement. This research is juridical-empirical research, which is descriptive in nature with a qualitative approach. The primary data source is the results of interviews with the Commissioner of PT. Setya Perkasa Graha Aditama and Mr Adi. Secondary data sources include information obtained from statutory regulations, fiqh principles, and interviews with related parties that support research data. The analysis technique for this research uses interactive analysis. The research results show that the completion of the rental agreement between PT. Setya Perkasa Graha Aditama and Mr. Adi have complied with the dispute resolution in the agreement in the form of negotiations. And the legal consequences of overmacht for the perpetrators of the rental agreement are: The lessee is free from the obligation to fulfill the performance as long as he is still in a state of overwork. Or it is allowed to